INNOVATIVE TECHNOLOGICAL SOLUTIONS IN MODERN FILM PRODUCTION: FROM IDEA TO RELEASE (American Journal of Technology and Applied Sciences, 2024)
This article analyzes modern innovative technological solutions in film production, covering all stages of filmmaking, from concept to release. It examines digital pre- production tools, virtual production and autonomous filming technologies, algorithmic editing and the use of artificial intelligence in post-production , as well as modern screening formats and new release methods.